PEMBELAJARAN DARING NEW NORMAL COVID-19 SESUAI KETENTUAN KESEJAHTERAAN ANAK DAERAH SUSAH AKSESBILITAS - Atikah Dannah Lestari; Wahyuni Retnowulandari (Reformasi Hukum Trisakti, 2023)
Children's rights under Law No. 4 of 1979, specifically the right to education, were not fully upheld in online learning during the Coronavirus Disease 2019 (Covid-19) period. The formulation of the issue highlighted in this study is how to comply with Law No. 4 of 1979's provisions on child welfare with relation to online learning during the new typical era of Covid-19, and what child welfare initiatives have been undertaken by the Regional Government? The type of data used in the descriptive analytical normative legal research approach is secondary data containing the results of interviews. This study was carried out in a qualitative analysis with deductive conclusions drawn. The results of the research and discussion show that the welfare of the children of SDN 003 Sabang Mawang in education has not been properly met due to various factors that hinder the fulfillment of children's rights, in this case parents, government and society are still trying to make efforts to fulfill children's welfare. The conclusion of this study is that during the new normal period of Covid-19 in areas where accessibility is difficult it requires special attention from the government in infrastructure regarding education.